Pendidikan dan Pembentukan Karakter Peserta Didik Perspektif Teologi Pendidikan Islam - Irawan, Feri Indra; Cucu Munawaroh; Hilman Rasyid; Hasan Basri (Journal of Education and Social Culture, 2025)
This study aims to systematically examine the concepts and practices of character education for students from the perspective of Islamic educational theology. Using a Systematic Literature Review (SLR) approach, 37 relevant scholarly articles published between 2013 and 2023 were thematically analyzed. The findings indicate that character formation in Islamic education is rooted in theological principles such as tauhid (divine unity), fitrah (natural disposition), and amanah (moral responsibility). Core Islamic character values include faith, piety, honesty, trustworthiness, patience, and justice. Implementation strategies include exemplary modeling (uswah), habituation (ta’dib), and spiritual reflection (muhasabah). Teachers play a crucial role as moral and spiritual exemplars in shaping students’ character. This study affirms that the theological approach in Islamic education significantly contributes to the development of holistic and transcendent character. The findings serve as a theoretical and practical reference for enhancing character education in Islamic educational institutions.